Community-based student support system for improving primary education quality - Urai Kangkorn; Piangkae Poophayang; Terdsak Suphundee (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
This research and development study aimed to: (1) examine current and desired conditions and priority needs for developing a community-based student support system in primary schools; (2) develop and validate the proposed model; (3) examine the effects of model implementation on teachers’ knowledge and supervisory practices; and (4) evaluate the model’s feasibility and usefulness from stakeholders’ perspectives.The study was conducted in four phases. Phase 1 involved a needs assessment with 387 stakeholders. The findings indicated moderate current conditions and high desired conditions, with systematic student data management identified as the highest priority need. Phase 2 focused on model development and expert validation. The model received high to highest ratings for accuracy and appropriateness. Phase 3 implementation with 30 teachers revealed that posttest scores were significantly higher than pretest scores at the .05 level (p .001). Teachers’ supervisory-related behaviors were rated at the highest level, and stakeholder satisfaction was high level. Phase 4 evaluation confirmed high feasibility and usefulness. The findings demonstrate that the developed model is conceptually sound, practically feasible, and effective in strengthening community-based student support mechanisms in primary education.